2010
DOI: 10.1621/nrs.08004
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ1 and LXRα face a new regulator of macrophage cholesterol homeostasis and inflammatory responsiveness, AEBP1

Abstract: Peroxisome proliferator-activated receptor γ1 (PPARγ1) and liver X receptor α (LXRα) are nuclear receptors that play pivotal roles in macrophage cholesterol homeostasis and inflammation; key biological processes in atherogenesis. The activation of PPARγ1 and LXRα by natural or synthetic ligands results in the transactivation of ABCA1, ABCG1, and ApoE; integral players in cholesterol efflux and reverse cholesterol transport. In this review, we describe the structure, isoforms, expression pattern, and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 265 publications
(397 reference statements)
2
65
0
2
Order By: Relevance
“…In this study, we observed that oxLDL induced the expression of UFM1 in human primary monocytes and THP-1 cells. These from its imperative role in controlling macrophage cholesterol homeostasis 45,46) . Interestingly, pretreatment with LXR siRNA dramatically reversed the UFM1-induced reduction of p roinflammatory cytokine secretion, consistent with a recent report by Majdalawieh et al 55) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we observed that oxLDL induced the expression of UFM1 in human primary monocytes and THP-1 cells. These from its imperative role in controlling macrophage cholesterol homeostasis 45,46) . Interestingly, pretreatment with LXR siRNA dramatically reversed the UFM1-induced reduction of p roinflammatory cytokine secretion, consistent with a recent report by Majdalawieh et al 55) .…”
Section: Discussionmentioning
confidence: 99%
“…Because ABCG1 and ABCA1 are regulated by the nuclear receptor LXR [43][44][45][46] , we further examined whether the key transcription factor LXR is involved in the UFM1-induced expression of ABCA1 and ABCG1. First, we detected the LXR expression in LV-UFM1 and sh-UFM macrophages by western blot analysis.…”
Section: Ufm1 Induces Lxr Activation In Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…PPAR␥ heterodimerizes with the 9-cis-retinoic acid receptor (RXR) to form a transcription factor that binds to peroxisome proliferator response elements (PPREs) in the promoter region of target genes (30). PPAR␥ modulates many functions of macrophages, such as promoting cell differentiation (31), regulating cholesterol homeostasis (32), and antagonizing expression of proinflammatory genes (32,33). Recent findings indicate that PPAR␥ activation functions as a signaling mechanism for the anti-angiogenesis and anti-inflammatory function of PEDF (34,35).…”
Section: Pigment Epithelium-derived Factor (Pedf)mentioning
confidence: 99%
“…Our findings strongly suggest that macrophage AEBP1 plays a critical role in the development of atherosclerosis. The potential pro-atherogenic properties of AEBP1 may be a byproduct of a vital interplay of its ability to antagonize PPARγ1 and LXRα cholesterol efflux functions in macrophages and its ability to promote inflammation via enhanced NF-κB transcriptional activity (39,40). We anticipate that AEBP1 may serve as a molecular candidate toward the development of therapeutic strategies to ameliorate or attenuate atherogenesis.…”
Section: Discussionmentioning
confidence: 99%